"On-Water" Catalyst-Free Ecofriendly Synthesis of the Hantzsch Dihydropyridines. (12th August 2012) - Pramanik, Amit; Saha, Manabendra; Bhar, Sanjay
Abstract : An eco-friendly "on-water" protocol for efficient catalyst-free synthesis of the Hantzsch dihydropyridines from aryl, heteroaryl, alkyl, and vinylogous aldehydes has been developed with minimum auxiliary substances, toxic reagents, organic solvents, and disposal problems.